A high-strength fiber-reinforced fluoroplastic film and preparation method thereof
By mixing materials such as sepiolite, basalt and glass fiber in a specific proportion, and combining ETFE film for double-sided coating and hot pressing, the problem of fluoroplastic film being easily damaged under high tension span is solved, improving its strength and durability, and reducing production costs.
Patent Information
- Application Number
- CN202510251560.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fluoroplastic films are prone to breakage or slack under high tension spans, and have low production efficiency and high cost, and insufficient market acceptance.
Sepiolite and basalt fibers were mixed in a 1:1 ratio, and glass fibers, sodium silicate and silicon fluoride were added, and a high-strength fiber layer was formed by ball milling and stirring, and double-sided coating and hot pressing were combined with ETFE film.
It improves the overall strength and durability of fluoroplastic film, enhances its tensile strength and flexural properties, and the production process is relatively simple, suitable for large-scale industrial production, reducing costs.
Smart Images

Figure CN119773336A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluoroplastic films and relates to a high-strength fiber-reinforced fluoroplastic film and a preparation method thereof. Background Art
[0002] Fluoroplastic films are widely used in outdoor permanent building structures due to their excellent weather resistance, flame retardancy and high light transmittance, such as ETFE film, FEP film, PTFE film, PVDF film, etc. The introduction of film building structures has greatly improved the creative space of architects. Fluoroplastic also has the disadvantages of insufficient strength and easy creep. Therefore, when designing membrane structures, designers need to consider the tension span of the film. If the tension span is too large, it is easy to cause the film to break or become loose after long-term use. In order to improve the overall modulus and strength of the membrane material, it is necessary to combine high-strength fiber materials and fluoroplastic films to meet the requirements of high strength and high light transmittance.
[0003] There are two main solutions now: Solution 1: Coat the surface of the high-strength fiber mesh with PTFE emulsion, form a PTFE layer on the surface of the fiber mesh after high-temperature sintering, and use the modified PTFE film as the surface coating and high-strength fiber for high-temperature pressing; Solution 2: A PVDF coating layer is extruded on the surface of the high-strength fiber. The PVDF coating layer is woven into a mesh cloth. The mesh cloth and the PVDF film are pressed at high temperature to make a high-strength composite PVDF membrane material.
[0004] The main disadvantage of Option 1 is that a relatively thin PTFE coating is formed on the fiber mesh cloth after high-temperature sintering after dip coating. Due to its small thickness and insufficient overall bonding strength after high-temperature pressing of the PTFE film, the reinforcing fibers behind the surface PTFE film are prone to detachment during later use.
[0005] The main disadvantage of Option 2 is that the production efficiency is very low. First, a layer of PVDF resin needs to be coated on the surface of the high-strength fiber by extrusion (just like wire extrusion). The fiber coated with PVDF needs to be woven into a grid, and finally made into a finished product by hot pressing. The bonding layer on the surface of the fiber made in this way is relatively thick, and the overall bonding strength will be much higher than that of Option 1. However, due to the low efficiency, the final product price is high and the market acceptance is insufficient. Summary of the invention
[0006] The object of the present invention is to provide a high-strength fiber-reinforced fluoroplastic film and a preparation method thereof, which has the characteristics of high strength.
[0007] The purpose of the present invention can be achieved through the following technical solutions: A high-strength fiber-reinforced fluoroplastic film, the fluoroplastic film comprising upper and lower layers of ethylene-tetrafluoroethylene copolymer ETFE films and a high-strength fiber layer in the middle. The preparation method of the high-strength fiber layer is as follows: S1.1: Sepiolite and basalt fiber were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 2 h to obtain a mixture A; S1.2: Mix mixture A and glass fiber in a mass ratio of (0.5-1):1, increase the ball mill speed to 600 r / min and continue grinding for 1 h to obtain mixture B; S1.3: Disperse the mixture B in deionized water, heat the deionized water to 70-120°C, stir at a speed of 180 r / min, and stir for 0.5-1 h, filter, and dry at 80°C for 12 h to obtain pretreated mixed fiber C; S1.4: Sodium silicate was dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 10%, and 3wt% silicon fluoride was added, and the mixture was stirred at a speed of 180r / min for 1h to obtain a mixture D, and the mixed fiber C was dispersed in the mixture D, and the mixture was stirred at a speed of 200r / min for 2h. After the stirring was completed, the mixed fiber E was obtained; S1.5: Spreading the mixed fiber E into a mesh structure and drying it at room temperature to form a fiber grid; S1.6: A layer of asphalt with a concentration of 20-30% is uniformly coated on the surface of the fiber mesh, and dried by a laser drying method to obtain the high-strength fiber layer.
[0008] Furthermore, the particle size of the mixture A obtained by grinding in S1.1 is 500 mesh.
[0009] Furthermore, the particle size of the mixture B obtained by grinding in S1.2 is 800 mesh.
[0010] Furthermore, the mass ratio of the mixed fiber C and the mixture D in S1.4 is 1:1.
[0011] Furthermore, the parameters of the laser drying method in S1.6 are: laser power 300W, temperature 60°C, and irradiation time 3-5min.
[0012] A method for preparing a high-strength fiber-reinforced fluoroplastic film, the specific process of the method for preparing the high-strength fiber-reinforced fluoroplastic film is as follows: Plasma treatment is performed on one surface of the ETFE film, and the plasma-treated side is covered on both sides of the high-strength fiber layer. High-temperature pressing rollers are used to perform hot pressing in the form of double-sided lamination to obtain the high-strength fiber-reinforced fluoroplastic film.
[0013] Furthermore, the ETFE film has a thickness of 100 μm.
[0014] Furthermore, the parameters of the plasma treatment are: surface treatment with plasma generated by a 400W power source for 80 to 100 seconds in air at room temperature and pressure.
[0015] Furthermore, the hot pressing parameters are hot pressing at a force of 5KN~10KN for 100~500s.
[0016] Furthermore, the thickness of the high-strength fiber-reinforced fluoroplastic film is 1.2 mm.
[0017] The present invention prepares a high-strength fiber layer, which has the characteristic of high tensile strength and is suitable for various environments.
[0018] Both sepiolite and basalt fibers have high strength. Through ball milling and mixing, their performance is further optimized to form a mixture with high strength and high durability. The addition of the two effectively enhances the overall strength and durability of the fiber layer. In the present invention, sepiolite and basalt fibers are mixed in a ratio of 1:1. The basalt fibers themselves have high tensile strength and reinforcement effect, and the addition of sepiolite fibers can form chemical bonds or physical entanglements with the basalt fibers through their silicate structure, thereby further enhancing the interaction force between the fibers and improving the overall strength. The 1:1 ratio helps to form a more uniform and dense fiber network during the grinding and dispersion process. This network structure can more effectively transmit and disperse stress, thereby improving the overall bearing capacity of the fiber layer. If the ratio of sepiolite to basalt fiber is too high, the overall strength of the fiber layer will decrease, because the strength of sepiolite fiber is lower than that of basalt fiber, and too much sepiolite fiber will affect the adhesion and uniformity between fibers, reducing the overall performance of the fiber layer; if the ratio is too low, the durability of the fiber will be reduced. This is because although basalt fiber itself has high strength, it lacks the reinforcing effect and chemical stability of sepiolite, which will cause the performance of the fiber layer to decrease after long-term use. Too little sepiolite cannot fully play its role in improving the fiber network structure and improving durability. Therefore, sepiolite and basalt fiber are mixed in a ratio of 1:1, which can fully utilize the complementary effects of the two advantages to form a high-strength and high-durability fiber layer. However, too high or too low a ratio may affect the overall performance and application effect of the fiber layer.
[0019] The present invention further adds glass fiber, which improves the bending and impact resistance of the fiber layer. This is because glass fiber has a high elastic modulus and tensile strength, which can effectively resist external forces and prevent the fiber layer from breaking or deforming; sepiolite, basalt and glass fiber are closely combined through ball milling and subsequent treatment. These fibers are intertwined in the fiber layer and jointly withstand external forces, which improves the overall strength and durability of the fiber layer.
[0020] The addition of sodium silicate and silicon fluoride enhances the water resistance and chemical stability of the fiber layer. Sodium silicate can form chemical adsorption on the fiber surface to form an inorganic fiber reinforcement system, thereby improving the water resistance and physical strength of the fiber. The addition of silicon fluoride can further enhance this chemical adsorption effect and improve the overall stability of the fiber layer. When sodium silicate comes into contact with the fiber, the silicate ions react with the hydroxyl or amine groups on the fiber surface to form silicate ester bonds or silicon oxygen bonds. These chemical bonds can firmly attach sodium silicate to the fiber surface, thereby enhancing the bonding force between the fibers. In addition, sodium silicate can also form a thin film on the fiber surface, which can fill the tiny pores between the fibers, making the fiber structure more compact, thereby improving the strength and wear resistance of the fiber. Silicon fluoride can be used as a silicate curing agent to reduce the curing time and increase the curing strength. The addition of silicon fluoride can also improve the acid resistance, alkali resistance and heat resistance of the fiber, thereby improving the stability of the fiber in harsh environments. Sodium silicate and silicon fluoride can react chemically in water to generate compounds with higher strength. These compounds can further enhance the bonding force between fibers and make the fiber structure stronger. Sodium silicate mainly enhances the physical bonding and chemical bonding between fibers, while silicon fluoride mainly improves the weather resistance and stability of fibers. The two complement each other and jointly improve the comprehensive performance of fibers; in addition, sodium silicate and silicon fluoride form a chemical adsorption layer on the fiber surface. This chemical adsorption not only enhances the water resistance and chemical stability of the fiber, but also promotes the close bonding between fibers. At the same time, this chemical adsorption layer can also prevent the fiber from being eroded and damaged by the external environment.
[0021] In order to further improve the strength of the fiber layer, the present invention coats a layer of asphalt on the surface of the fiber layer, which can provide additional waterproof, anti-corrosion and wear-resistant protection. Asphalt has good waterproof and corrosion resistance, and can form a protective film to prevent the fiber layer from being corroded by moisture and chemicals. After a layer of asphalt is evenly coated on the surface of the fiber grid, the asphalt can penetrate into the tiny pores between the fibers and form a tight bond with the fibers. This bond not only strengthens the physical connection between the fibers, but also improves the overall strength of the fiber layer through chemical adhesion. At the same time, asphalt itself has high viscosity and elasticity, and can absorb and disperse stress when subjected to external forces, thereby protecting the fibers from damage and further improving the durability of the fiber layer. The present invention controls the concentration of asphalt to be between 20% and 30%. If the concentration of asphalt is too high, its fluidity will be reduced, and it will not be easy to be evenly coated on the surface of the fiber mesh. If the concentration of asphalt is too thick, the fiber layer will become more brittle, and its flexibility and crack resistance will be reduced. In addition, a high concentration of asphalt may generate shrinkage stress during the drying process, causing cracks or peeling of the fiber layer. If the concentration of asphalt is too low, a sufficient adhesion layer cannot be formed, and the fibers cannot be effectively connected. A weak asphalt layer may not provide sufficient protection, making the fiber layer susceptible to erosion and damage by the external environment. A low concentration of asphalt may leave pores or defects after drying, reducing the overall strength and sealing of the fiber layer.
[0022] The sepiolite in the present invention was purchased from Jiangsu Aikang Biomedicine Research and Development Co., Ltd. with a purity of 95%; the basalt fiber in the present invention was purchased from Tai'an Senyang Composite Materials Co., Ltd. with a length of 6 mm; the glass fiber in the present invention was purchased from Hubei Yunmei Technology Co., Ltd. with a purity of 99%; the sodium silicate in the present invention was purchased from Hubei Chengfeng Chemical Co., Ltd. with a purity of 99%; the silicon fluoride in the present invention was purchased from Suzhou Siso New Materials Co., Ltd. with a purity of 97%; the asphalt in the present invention was purchased from Chengdu Huaxia Chemical Reagent Co., Ltd. with a purity of 99%.
[0023] Beneficial effects of the present invention: The present invention can change the chemical properties and physical structure of the surface of the ETFE film by plasma treatment on one side surface, increase the surface roughness and polar groups, and these changes help to form stronger chemical bonding and physical bonding between the ETFE film and the high-strength fiber layer, thereby improving the bonding force between the two; the high-strength fiber layer is used as a reinforcing material, and the ETFE film and the high-strength fiber layer are tightly combined by double-sided lamination and hot pressing, so that the film can better disperse stress when subjected to external force, thereby improving the overall strength, and the prepared fluoroplastic film maintains the transparency, heat resistance and corrosion resistance of ETFE while also enhancing its strength; the preparation method is relatively simple and easy to control, suitable for large-scale industrial production, and the double-sided lamination and hot pressing processes can be carried out continuously, thereby shortening the production cycle and improving the production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0025] Figure 1 Schematic diagram of the method for preparing fluoroplastic film of the present invention. DETAILED DESCRIPTION
[0026] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0027] Example 1 A high-strength fiber-reinforced fluoroplastic film, the fluoroplastic film comprising upper and lower layers of ethylene-tetrafluoroethylene copolymer ETFE films and a high-strength fiber layer in the middle. The preparation method of the high-strength fiber layer is as follows: S1.1: Sepiolite and basalt fiber were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 2 h to obtain a mixture A, wherein the particle size of the mixture A was 500 mesh; S1.2: Mix mixture A and glass fiber in a mass ratio of 1:1, increase the ball mill speed to 600 r / min and continue grinding for 1 hour to obtain mixture B, the particle size of mixture B is 800 mesh; S1.3: Disperse the mixture B in deionized water, heat the deionized water to 100°C, stir at a speed of 180 r / min for 1 hour, filter, and dry at 80°C for 12 hours to obtain pretreated mixed fiber C; S1.4: Sodium silicate was dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 10%, and then 3wt% silicon fluoride was added, and the mixture was stirred at a speed of 180r / min for 1h to obtain a mixture D, and mixed fiber C was dispersed in the mixture D, and the mass ratio of mixed fiber C to mixture D was 1:1. The mixture was stirred at a speed of 200r / min for 2h, and after the stirring was completed, mixed fiber E was obtained; S1.5: Spreading the mixed fiber E into a mesh structure and drying it at room temperature to form a fiber grid; S1.6: A layer of asphalt with a concentration of 20% is uniformly coated on the surface of the fiber mesh, and then dried by a laser drying method. The laser drying method parameters are laser power 300 W, temperature 60° C., and irradiation time 4 min to obtain the high-strength fiber layer.
[0028] The specific process of the preparation method of the high-strength fiber-reinforced fluoroplastic film is as follows: The surface of one side of the ETFE film is plasma treated, the thickness of the ETFE film is 100 μm, the parameters of the plasma treatment are: at room temperature and pressure, in air, the surface is treated with plasma generated by a 400 W power supply for 100 seconds, the plasma-treated side is covered on both sides of the high-strength fiber layer, and hot pressing is performed in the form of double-sided lamination, and the hot pressing parameters are hot pressing with a force of 7 KN for 300 seconds to obtain a high-strength fiber-reinforced fluoroplastic film with a thickness of 1.2 mm. The preparation method of the fluoroplastic film of the present invention is referred to Figure 1 .
[0029] Example 2 A high-strength fiber-reinforced fluoroplastic film, the fluoroplastic film comprising upper and lower layers of ethylene-tetrafluoroethylene copolymer ETFE films and a high-strength fiber layer in the middle. The preparation method of the high-strength fiber layer is as follows: S1.1: Sepiolite and basalt fiber were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 2 h to obtain a mixture A, wherein the particle size of the mixture A was 500 mesh; S1.2: Mix mixture A and glass fiber in a mass ratio of 0.5:1, increase the ball mill speed to 600 r / min and continue grinding for 1 hour to obtain mixture B, the particle size of mixture B is 800 mesh; S1.3: Disperse the mixture B in deionized water, heat the deionized water to 70°C, stir at a speed of 180 r / min for 1 hour, filter, and dry at 80°C for 12 hours to obtain pretreated mixed fiber C; S1.4: Sodium silicate was dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 10%, and then 3wt% silicon fluoride was added, and the mixture was stirred at a speed of 180r / min for 1h to obtain a mixture D, and mixed fiber C was dispersed in the mixture D, and the mass ratio of mixed fiber C to mixture D was 1:1. The mixture was stirred at a speed of 200r / min for 2h, and after the stirring was completed, mixed fiber E was obtained; S1.5: Spreading the mixed fiber E into a mesh structure and drying it at room temperature to form a fiber grid; S1.6: A layer of asphalt with a concentration of 30% is uniformly coated on the surface of the fiber mesh, and then dried by a laser drying method. The laser drying method parameters are laser power 300 W, temperature 60° C., and irradiation time 5 min to obtain the high-strength fiber layer.
[0030] The specific process of the preparation method of the high-strength fiber-reinforced fluoroplastic film is as follows: The surface of one side of the ETFE film is plasma treated, the thickness of the ETFE film is 100 μm, the parameters of the plasma treatment are: at room temperature and pressure, in air, the surface is treated with plasma generated by a 400 W power supply for 80 seconds, the plasma-treated side is covered on both sides of the high-strength fiber layer, and hot pressing is performed in the form of double-sided lamination, the hot pressing parameters are hot pressing with a force of 5 KN for 500 seconds, and a high-strength fiber-reinforced fluoroplastic film with a thickness of 1.2 mm is obtained. The preparation method of the fluoroplastic film of the present invention refers to Figure 1 .
[0031] Example 3 A high-strength fiber-reinforced fluoroplastic film, the fluoroplastic film comprising upper and lower layers of ethylene-tetrafluoroethylene copolymer ETFE films and a high-strength fiber layer in the middle. The preparation method of the high-strength fiber layer is as follows: S1.1: Sepiolite and basalt fiber were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 2 h to obtain a mixture A, wherein the particle size of the mixture A was 500 mesh; S1.2: Mix mixture A and glass fiber in a mass ratio of 0.5:1, increase the ball mill speed to 600 r / min and continue grinding for 1 hour to obtain mixture B, the particle size of mixture B is 800 mesh; S1.3: Disperse the mixture B in deionized water, heat the deionized water to 120°C, stir at a speed of 180 r / min, and stir for 0.5 h, filter, and dry at 80°C for 12 h to obtain pretreated mixed fiber C; S1.4: Sodium silicate was dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 10%, and then 3wt% silicon fluoride was added, and the mixture was stirred at a speed of 180r / min for 1h to obtain a mixture D, and mixed fiber C was dispersed in the mixture D, and the mass ratio of mixed fiber C to mixture D was 1:1. The mixture was stirred at a speed of 200r / min for 2h, and after the stirring was completed, mixed fiber E was obtained; S1.5: Spreading the mixed fiber E into a mesh structure and drying it at room temperature to form a fiber grid; S1.6: A layer of asphalt with a concentration of 20% is uniformly coated on the surface of the fiber mesh, and then dried by a laser drying method. The laser drying method parameters are laser power 300W, temperature 60°C, and irradiation time 3 minutes to obtain the high-strength fiber layer.
[0032] The specific process of the preparation method of the high-strength fiber-reinforced fluoroplastic film is as follows: The surface of one side of the ETFE film is plasma treated, the thickness of the ETFE film is 100 μm, the parameters of the plasma treatment are: at room temperature and pressure, in air, the surface is treated with plasma generated by a 400 W power supply for 100 seconds, the plasma-treated side is covered on both sides of the high-strength fiber layer, and hot pressing is performed in the form of double-sided lamination, and the hot pressing parameters are hot pressing with a force of 10 KN for 100 seconds to obtain a high-strength fiber-reinforced fluoroplastic film with a thickness of 1.2 mm. The preparation method of the fluoroplastic film of the present invention is referred to Figure 1 .
[0033] Comparative Example 1 In this comparative example, no sepiolite is added in the preparation of the high-strength fiber layer, and the remaining steps are consistent with those in Example 1.
[0034] Comparative Example 2 In this comparative example, basalt fiber is not added in the preparation of the high-strength fiber layer, and the remaining steps are consistent with those in Example 1.
[0035] Comparative Example 3 In the preparation of the high-strength fiber layer in this comparative example, the ratio of sepiolite to basalt fiber is 2:1, and the remaining steps are consistent with Example 1.
[0036] Comparative Example 4 In the preparation of the high-strength fiber layer in this comparative example, the ratio of sepiolite to basalt fiber is 1:2, and the remaining steps are consistent with Example 1.
[0037] Comparative Example 5 In this comparative example, no glass fiber is added in the preparation of the high-strength fiber layer, and the remaining steps are consistent with those in Example 1.
[0038] Comparative Example 6 In this comparative example, no sodium silicate was added in the preparation of the high-strength fiber layer, and the remaining steps were consistent with those in Example 1.
[0039] Comparative Example 7 In this comparative example, silicon fluoride is not added in the preparation of the high-strength fiber layer, and the remaining steps are consistent with those in Example 1.
[0040] Comparative Example 8 In this comparative example, no asphalt is coated during the preparation of the high-strength fiber layer, and the remaining steps are consistent with those in Example 1.
[0041] Comparative Example 9 In this comparative example, the concentration of asphalt coated in the preparation of the high-strength fiber layer is 10%, and the remaining steps are consistent with Example 1.
[0042] Comparative Example 10 In this comparative example, the concentration of asphalt coated in the preparation of the high-strength fiber layer is 50%, and the remaining steps are consistent with Example 1.
[0043] Comparative Example 11 In the preparation process of the high-strength fiber-reinforced fluoroplastic film in this comparative example, the surface of one side of the ETFE film is not subjected to plasma treatment, and the remaining steps are consistent with those in Example 1.
[0044] The tensile strength performance of the embodiments and comparative examples was tested with reference to the standard ISO 527-1-2012. The experimental results are summarized in the following table:
[0045] It can be seen from the experimental data that the embodiments of the present invention have better tensile strength. The addition of sepiolite and basalt fiber in a ratio of 1:1 in the fiber layer can effectively improve the tensile strength of the fluoroplastic film; the addition of glass fiber, sodium silicate and silicon fluoride can also effectively improve the tensile strength of the fluoroplastic film; the coating of 20-30% asphalt and the plasma treatment during the preparation process also have a certain effect on the tensile strength of the fluoroplastic film.
[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high-strength fiber-reinforced fluoroplastic film, characterized in that: The fluoroplastic film comprises two layers of ethylene-tetrafluoroethylene copolymer ETFE film and a middle high-strength fiber layer. The preparation method of the high-strength fiber layer is as follows: S1.1: Sepiolite and basalt fiber were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 2 h to obtain a mixture A; S1.2: Mix mixture A and glass fiber in a mass ratio of (0.5-1):1, increase the ball mill speed to 600 r / min and continue grinding for 1 h to obtain mixture B; S1.3: Disperse the mixture B in deionized water, heat the deionized water to 70-120°C, stir at a speed of 180 r / min, and stir for 0.5-1 h, filter, and dry at 80°C for 12 h to obtain pretreated mixed fiber C; S1.4: Sodium silicate was dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 10%, and 3wt% silicon fluoride was added, and the mixture was stirred at a speed of 180r / min for 1h to obtain a mixture D, and the mixed fiber C was dispersed in the mixture D, and the mixture was stirred at a speed of 200r / min for 2h. After the stirring was completed, the mixed fiber E was obtained; S1.5: Spreading the mixed fiber E into a mesh structure and drying it at room temperature to form a fiber grid; S1.6: uniformly coating a layer of asphalt with a concentration of 20-30% on the surface of the fiber mesh, and drying by a laser drying method to obtain the high-strength fiber layer; The specific process of the preparation method of the high-strength fiber-reinforced fluoroplastic film is as follows: Plasma treatment is performed on one surface of the ETFE film, and the plasma-treated side is covered on both sides of the high-strength fiber layer. High-temperature pressing rollers are used to perform hot pressing in the form of double-sided lamination to obtain the high-strength fiber-reinforced fluoroplastic film.
2. A high-strength fiber-reinforced fluoroplastic film according to claim 1, characterized in that: The particle size of the mixture A obtained by grinding in S1.1 is 500 mesh.
3. A high-strength fiber-reinforced fluoroplastic film according to claim 1, characterized in that: The particle size of the mixture B obtained by grinding in S1.2 is 800 mesh.
4. A high-strength fiber-reinforced fluoroplastic film according to claim 1, characterized in that: The mass ratio of the mixed fiber C and the mixture D in S1.4 is 1:
1.
5. The high-strength fiber-reinforced fluoroplastic film according to claim 1, characterized in that: The parameters of the laser drying method in S1.6 are: laser power 300 W, temperature 60° C., and irradiation time 3 to 5 min.
6. A high-strength fiber-reinforced fluoroplastic film according to claim 1, characterized in that: The thickness of the ETFE film is 100 μm.
7. The high-strength fiber-reinforced fluoroplastic film according to claim 1, characterized in that: The parameters of the plasma treatment are: at room temperature and pressure, in air, the surface is treated with plasma generated by a 400W power source for 80 to 100 seconds.
8. The high-strength fiber-reinforced fluoroplastic film according to claim 1, characterized in that: The hot pressing parameters are hot pressing at a force of 5KN~10KN for 100~500s.
9. The high-strength fiber-reinforced fluoroplastic film according to claim 1, characterized in that: The thickness of the high-strength fiber-reinforced fluoroplastic film is 1.2 mm.